Cloning and expression of the fhu genes involved in iron(III)-hydroxamate uptake by Escherichia coli. - Fecker, L (1983)
Each of the four hydroxamate compounds, ferrichrome, aerobactin, rhodotorulic acid, and coprogen, known to transport ferric iron into Escherichia coli requires a specific outer membrane receptor protein. In addition, common transport functions for all four ferric hydroxamate compounds have been identified in the 3.5-min region of the linkage map and designated fhu. The fhu region was cloned into pBR322. By restriction analysis, Tn5 insertion mutations, and complementation studies between plasmid fragments and chromosomal mutants at least four loci in the order fhuA fhuC fhuD fhuB were found. The genetic products were determined in maxicells and minicells. fhuA codes for the known 78,000-dalton receptor protein and the 81,000-dalton precursor in the outer membrane, fhuC codes for a 30,000-dalton protein, and fhuD encodes a 26,000-dalton protein in the cytoplasmic membrane. No protein(s) could be assigned to the fhuB region. Truncated proteins derived from partial fhuA genes (68,000, 42,000, and 39,000 daltons) and a partial fhuD gene (24,000 daltons) and the strong polar effect on the expression of the genes indicated the direction of transcription to be from fhuA to fhuD.